O programa SAREH na educação hospitalar: concepções de educação, ensino, aprendizagem, aluno e professor em documentos oficiais - Andreolla, Evelin Stefanie Ferreira (2021)
The objective of the In-Hospital Education (IHE) is to promote the continuity of school studies for young people undertaking hospital care. This teaching modality is relatively new, and it is based on specific official documents which list the modality’s objectives and obligations. 13 years ago, it was installed in the State of Parana the Serviço de Atendimento à Rede de Escolarização Hospitalar (SAREH), which is organized according to legal documents that are responsible for determining its functioning rules. Parting from this context, this research is based on the following question: What are the conceptions of education, teaching, learning, student and teacher in the official documents that ground the SAREH program? In order to answer this question, the research’s main goal is to identify the characteristics of the ideas of education, teaching, learning, student and teacher in official documents that ground the IHE and the SAREH program. The theoretical and methodological approach embodied in this research is the Applied Linguistics, based on Moita-Lopes (2006). A documental analysis was also made (GIL, 2008) under the qualitative and interpretativist paradigm (FARACO, 2001; BORTONI-RICARDO, 2008). Regarding the theoretical basis, this research has its grounds on the conception of education of Freire (1987, 2002, 2009) and on the Bakhtin’s Circle theory (VOLOCHÍNOV; BAKHTIN, 1926; BAKHTIN, 2010, 2003; VOLOCHÍNOV, 2013, 2017, and the Brazilians, BRAIT, 2004, 2005, 2017, 2018; FARACO, 2007, 2009). Considering this theory, this study was oriented by the principles and procedures of the Dialogic Discourse Analysis (ADD) - Brait, 2018; Brait e Acosta Pereira, 2020. To enable an ADD, our corpus was composed of 7 legal documents that guide the organization of the SAREH program, from which some excerpts concerning the IHE were chosen. As results, regarding the conception of education, it was observed an emphasis on the idea of service or assistance and there is a valuation of the IHE as a different teaching modality. Considering the concept of teaching and learning there is a bigger emphasis on the learning process rather than in both processes as a compound. There is also a valuation considering “the teaching methodology” rather than the multiple and diverse methodologies that are demanded by the IHE. The concept of student is refracted by the documents under the signs “aluno”, “estudante” and “educando”, which valuate this social position in different ways. Regarding the concept of teacher, we observed a responsibility discourse upon the teachers concerning the teaching and learning process and the students’ interaction with the contents. However, there is also a discourse valuation of the teacher as the mediator of this process.